Exercise test is essential in LV-only fusion CRT pacing without right ventricle lead - Vacarescu C (Clinical Interventions in Aging, 2019)
Cristina Vacarescu,1 Dragos Cozma,1,2 Lucian Petrescu,1,2 Simona Dragan,1,2 Cristian Mornos,1,2 Simina Crisan,1,2 Horea Feier,1,2 Mihai-Andrei Lazar,1 Ramona Alina Cozlac,1,2 Constantin Tudor Luca1,21Cardiology Department, Victor Babeș University of Medicine and Pharmacy, Timișoara, Romania; 2Cardiology Department, Institute of Cardiovascular Diseases, Timișoara, RomaniaPurpose: Left ventricle (LV)-only pacing is non-inferior to biventricular pacing but permanent fusion pacing is needed to ensure cardiac resynchronization therapy (CRT) responsiveness. The role of systematic exercise testing (ET) in these patients has not been established. This study was designed to assess clinical and therapeutic implications (device programming/drugs) of systematic ET in patients requiring fusion-pacing CRT without an right ventricle (RV) lead.Methods: Consecutive patients with a right atrium/LV-only dual-chamber (DDD) pacing system were included. Prospective data were obtained: device interrogation, ET, and echocardiography at every 6-month follow-up visit. CRT assessment during ET included maximal heart rate, beat-to-beat echocardiography analysis of LV fusion pacing, LV loss of capture, and improvement in exercise capacity. If LV loss of capture or unsatisfactory LV fusion pacing occurred, reprogramming was individualized for each patient and ET redone.Results: A total of 55 patients (29 male) aged 62±11 years were included. During follow-up (39±18 months), a total of 235 ETs were performed, with mean exercise load 6.4±1.3 metabolic equivalents of task (118±35 W, maximal heart rate 119±17 beats/min). Twenty patients (36%) had inadequate pacing or loss of LV capture during ET, due to exceeding the maximum tracking rate (11%), chronotropic incompetence (7%), and LV pacing outside the fusion-pacing band (18%), caused by physiological shortening of the PR interval or exagerated LV preexcitation during maximum exercise. Post-ET CRT-device optimization included reprogramming of rate-adaptive atrioventricular interval (total decrease 23±8 ms), individualized programming of maximum tracking rate, or rate-response function. Drug optimization was performed in 32% of patients, and ET redone in 36%.Conclusion: In one of three ETs, an intervention in device and medication optimization was done to ensure a better outcome. Routine ET should be a standard approach to maximize fusion-pacing CRT response during follow-up.Keywords: cardiac resynchronization therapy, LV-only pacing, exercise test, constant fusion pacing